2022
DOI: 10.3390/ijms23179784
|View full text |Cite
|
Sign up to set email alerts
|

An Update on the Effects of Vitamin D on the Immune System and Autoimmune Diseases

Abstract: Vitamin D intervenes in calcium and phosphate metabolism and bone homeostasis. Experimental studies have shown that 1,25-dihydroxyvitamin D (calcitriol) generates immunologic activities on the innate and adaptive immune system and endothelial membrane stability. Low levels of serum 25-hydroxyvitamin D (25(OH)D) are associated with an increased risk of developing immune-related diseases such as psoriasis, type 1 diabetes, multiple sclerosis, and autoimmune diseases. Various clinical trials describe the efficacy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
76
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(82 citation statements)
references
References 347 publications
1
76
0
5
Order By: Relevance
“…It also modulates the adaptive response of Treg and Th2 lymphocytes through VDR activation and leads to their activation and increased production of anti-inflammatory cytokines [ 97 , 98 ]. Calcitriol decreases the production of pro-inflammatory cytokines by T1 lymphocytes [ 99 , 100 ], blocks the maturation of B lymphocytes and their transformation into effector B cells, and decreases their expression of MHC-II [ 101 , 102 ]. Furthermore, it has an immunosuppressive effect via the NFκB transcription factor [ 103 ].…”
Section: Discussionmentioning
confidence: 99%
“…It also modulates the adaptive response of Treg and Th2 lymphocytes through VDR activation and leads to their activation and increased production of anti-inflammatory cytokines [ 97 , 98 ]. Calcitriol decreases the production of pro-inflammatory cytokines by T1 lymphocytes [ 99 , 100 ], blocks the maturation of B lymphocytes and their transformation into effector B cells, and decreases their expression of MHC-II [ 101 , 102 ]. Furthermore, it has an immunosuppressive effect via the NFκB transcription factor [ 103 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our subgroup analysis also suggested significant interactions of anemia [31,32]. Further, low levels of 25(OH)D may increase the risk of immune-related diseases because they exert an immunomodulatory effect through nuclear vitamin D receptor expressed by antigen-presenting cells and activated T and B cells [33,34]. erefore, we screened the database for data from patients with immune diseases and hyperparathyroidism; after adjusting for these covariates, the results were generally consistent with those above, confirming that arthritis and rheumatism are not additional risk factors for reduced plasma 25(OH)D concentrations [35].…”
Section: Discussionmentioning
confidence: 54%
“…Early epidemiological studies have shown lower serum vitamin D levels in patients with psoriasis than healthy controls [12]. Administrating vitamin D supplementation led to reduced mortality in patients with psoriasis [17] and topical vitamin D analogues demonstrated effectiveness in treating psoriasis [9]. A recent prospective study suggested that low 25(OH)D level was associated with high risk of psoriasis using both cox proportional hazard model and MR analysis [27].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, C3-epimer of 25(OH)D 3 (C3-epi-25(OH)D 3 ), a vitamin D metabolite from 25(OH)D 3 through 3β to 3α isomerization transformation, can also affect the amount of bioactive vitamin D conversion [7]. Recent studies have shown that 25(OH)D and its relevant compounds are associated with many diseases, including cancers, kidney, infectious, and autoimmune diseases [8,9]. These findings suggest that vitamin D might play a role in calcium homeostasis, immune regulation, anti-bacterial, and anti-inflammation.…”
Section: Introductionmentioning
confidence: 99%